Phthalates exposure as environmental risk factor for type 2 diabetes mellitus - Munaya Fauziah; Suhartono Suhartono; Bagoes Widjanarko; Muhammad Hussein Gasem (Intelektual Pustaka Media Utama, 2023)
Phthalates exposure occurs in all areas, such as foods' plastic packaging, cosmetics, and others. Previous studies showed that phthalates are associated with the prevalence of T2DM. Type 2 Diabetes Mellitus (T2DM) is caused by a combination of defective insulin secretion by pancreatic β-cells and the insulin-resistance. This study aimed to investigate whether phthalate exposure is an environmental risk factor for T2DM. A case-control study was conducted among residents in the South Tangerang district from June 2020 to February 2021 using a purposive sampling technique. The cases were the patients diagnosed T2DM with HbA1c>6.5% random blood sugar>200 mg/dL, with history T2DM treatment. The respondents' urines were collected and evaluated using liquid chromatography/mass spectrometry (LC/MS). A total of 47 cases and 47 controls were recruited in the study. The lowest monomethyl phthalate (MEP) and mono (2-ethyl-5-hydroxyhexyl) phthalate (MEHHP) were 5.37 µg/L and 2.02 µg/L, respectively. On multivariable regression analysis, the high urinary MEP level (>131.91 µg/L) was independently associated with T2DM (OR: 3.754, 95% CI: 1.559–8.811, p-value: 0.002). MEP is an environmental risk factor for T2DM and likely has a significant impact on human health than MEHHP.